Are physical education lessons suitable for sport talent identification? A systematic review of the literature - Prieto-Ayuso, A.; Pastor-Vicedo, J. C.; González-Villora, S.; Fernández-Rio, J. (International Journal of Environmental Research and Public Health, 2020)
Objectives: The goal of this study was to shed light on the existent knowledge, internationally published over the last decade (2009-2019), on how to deal with talented children in physical education (PE). Methods: A mixed systematic review (SR) was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in the International Prospective Register of Systematic Reviews (PROSPERO), registration number: CRD42019117211. Study eligibility criteria: The articles included were selected using the following criteria: (a) studies published in peer-reviewed international journals; (b) studies published from 2009 to 2019 (both inclusive); (c) studies that included quantitative and/or qualitative methods and findings; (d) research conducted within school contexts; (e) articles that focused on both talent/gift and PE, and (f) studies published in English or Spanish. Results: A total of 11 articles were identified. Results showed a gradual change in both methods and instruments used for talent identification (TI) in PE, focused currently on children`s health and involvement in sports. Second, there is consensus on the lack of clarity in schools` policies and guidelines on how to deal with talented children in PE. Conclusions: Finally, there are alternative programs to elite athlete models that better fit in PE to deal with talented children and to avoid child disengagement in PE and sports.